Structure optimization and preliminary bioactivity evaluation of N-hydroxybenzamide-based HDAC inhibitors with Y-shaped cap. Issue 8 (1st May 2018) - Yu, Chenggong; He, Feng; Qu, Ying; Zhang, Qiuqiong; Lv, Jiahui; Zhang, Xiangna; Xu, Ana; Miao, Pannan; Wu, Jingde
Graphical abstract: Abstract: Histone deacetylase inhibitors (HDACIs) are effective small molecules in the treatment of human cancers. In our continuing efforts to develop novel N -hydroxyterephthalamide-based HDACIs, herein we report the design and development of a new class of N -hydroxybenzamide-based HDACIs. In this new class of analogs, we inserted an ethylene moiety in the linker and used indole as a part of the Y-shaped cap group. Biological characterization identified compounds 4o, 4p, 4q and 4t to show improved HDAC inhibition, while no isoform selectivity for HDACs was observed. These compounds also exhibited improved anti-proliferative activity against multiple cancer cell lines when compared to their parent compound and positive control SAHA.